2013
DOI: 10.1016/j.fuproc.2012.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Response surface methodology as an efficient tool for optimizing carbon adsorbents for CO2 capture

Abstract: Phenol-formaldehyde resins and a low-cost biomass residue, olive stones (OS), were used to prepare five activated carbons for CO 2 separation at atmospheric pressure, i.e., in post-combustion processes or from biogas and bio-hydrogen streams. Two phenolformaldehyde resins were synthesized: Resol, obtained by using alkaline environment, and Novolac, synthesized in the presence of an acid catalyst. Carbon precursors were prepared by mixing both resins with KCl or by mixing the Novolac resin with OS. The precurso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 16 publications
1
41
0
Order By: Relevance
“…Yan et al [49] developed carbon-encapsulated iron nanoparticles catalyst for the Fischer-Tropsch synthesis of biomass-derived syngas to liquid hydrocarbons. The catalyst was [39,40] synthesized by thermal treatment of iron-impregnated pine biochar at 1000 1C for 1 h. Biochar was obtained from a typical fast pyrolysis of pine wood and treated with HNO 3 to remove intrinsic ash and tar before impregnation. The Fischer-Tropsch synthesis results showed that the biochar-based iron nanoparticles catalyst had an efficiency of converting syngas into liquid hydrocarbons (CO conversion rate over 90% and liquid hydrocarbon selectivity as high as 70%), which is higher than other reported carbon supported iron catalysts for Fischer-Tropsch synthesis of syngas (2% to 88% CO conversion and 5% to 60% liquid hydrocarbon selectivity) [49].…”
Section: Catalyst For Conversion Of Syngas Into Liquid Hydrocarbonsmentioning
confidence: 99%
“…Yan et al [49] developed carbon-encapsulated iron nanoparticles catalyst for the Fischer-Tropsch synthesis of biomass-derived syngas to liquid hydrocarbons. The catalyst was [39,40] synthesized by thermal treatment of iron-impregnated pine biochar at 1000 1C for 1 h. Biochar was obtained from a typical fast pyrolysis of pine wood and treated with HNO 3 to remove intrinsic ash and tar before impregnation. The Fischer-Tropsch synthesis results showed that the biochar-based iron nanoparticles catalyst had an efficiency of converting syngas into liquid hydrocarbons (CO conversion rate over 90% and liquid hydrocarbon selectivity as high as 70%), which is higher than other reported carbon supported iron catalysts for Fischer-Tropsch synthesis of syngas (2% to 88% CO conversion and 5% to 60% liquid hydrocarbon selectivity) [49].…”
Section: Catalyst For Conversion Of Syngas Into Liquid Hydrocarbonsmentioning
confidence: 99%
“…Synthesis was conducted following two different routes, acid (hydrochloric acid, 37 wt% HCl solution) and basic (sodium hydroxide, NaOH) catalysis for the Novolac and the Resol resins, respectively. Details on the synthesis of the PF resins can be found elsewhere [18]. Carbon precursors were prepared from the aforementioned resins, and potassium chloride (KCl) was incorporated as inorganic additive.…”
Section: Synthesis Of Carbon Precursorsmentioning
confidence: 99%
“…Previous works carried out in our research group have demonstrated the relationship between the volume of narrow micropores of less than 0.7 nm and CO 2 uptake at atmospheric pressure [20]. Response surface methodology was performed to obtain the optimum conditions of activation with CO 2 that maximise CO 2 adsorption at atmospheric pressure for each precursor (details can be found in [18]). Activation with CO 2 was conducted in a tubular furnace with a CO 2 flowrate of 10 mL¨min´1.…”
Section: Production Of Microporous Carbonsmentioning
confidence: 99%
“…For the olive stones derived carbon (OS-AC) a conventional two-step procedure was pursued, including prior carbonization under inert atmosphere followed by activation in CO 2 . More details on the production of this sample can be found in a previous paper from our group [5]. It must be noted that this sample was produced by addition of a phenol-formaldehyde resin to the olive stones prior to carbonization and subsequent activation in CO 2 .…”
Section: Methodsmentioning
confidence: 99%